PENGARUH MODEL E-JIGSAW LEARNING UNTUK MENINGKATKAN KEMAMPUAN KOLABORASI MAHASISWA - Laifa Rahmawati; Jumadi Jumadi; Jaslin Ikhsan (Program Studi PGSD Universitas Flores, 2023)
The purpose of this study was to investigate the effectiveness of the e-jigsaw learning model to improve student collaboration skills. This research is an educational development research which is adapted from the development model according to Borg & Gall. The instrument used in this research is a collaboration skills questionnaire. The skills assessment was carried out for first semester students where two classes came from a state university and one class came from a private university. The results of the development are e-jigsaw learning learning model products. From the results of the research and development stages that have been carried out, it can be concluded that the e-jigsaw learning model is effective for improving collaboration skills.